The unity of cognitive and emotional aspects in modern psychotherapy - E. N. Rastorgueva (Вестник университета)
This article considers the role of emotional and cognitive aspects in modern areas of psychotherapy. It reveals long-term psychotherapeutic effects of incoherent dealing with client’s feelings and thoughts, based on actual case studies in modern psychotherapy and reflected in the literature on the subject. The analysis of psychotherapeutic texts reveals authors’ statements contradicting the general knowledge of feelings and emotions and suggests ways of eliminating such contradictions and simplifications. The article also considers how warping towards rationality can go unnoticed, to the detriment of dealing with feelings, and how the self-improvement process can lose its integrity, causing a distortion of basic psychological literacy instead of its enhancement. The article outlines and justifies two attitudes that are proposed to be developed among clients in any form and area of psychotherapy: the attitudes to live through their feelings and then release their unwanted feelings. We describe new psychological aspects in the process of living through one’s feelings in general and in the process of psychotherapy in particular. The integration of basic psychological knowledge of emotional intelligence into the theory and practice of various areas of psychotherapy can significantly improve the work of practicing psychologists and psychotherapists with clients and can effectively contribute to the convergence of different areas of psychotherapy.